Fertilización de alfalfa en suelos de la región semiárida Argentina (Semiárida, 2020)
The objetive of the present study which was carried out in the south of Córdoba is the evaluation of the response of alfalfa production to N, P and S fertilization in simple and mixes applications. The experiment consists in cross-banded applications of N, P and S at rates  of 34.5; 65 and 37.5 Kg respectively, resulting in the folIowing treatments: NPA, NP, N, P, S and Control. Dry matter production was measured in three cuts of 1 m2 portions of the pasture.  There was no statistically significant yield response to fertilization in any treatment. Further analysis showed that rainfall was very deficient in the period, possibly limiting alfalfa growth and yield response to fertilization. A very marked relation between dry matter production and soil moisture content was encountered, indicating that moisture was the limiting growth factor.Director: Ing. Agr. Elke Noellemeyer. Cátedra de Edafología, Manejo, y Conservación y Fertilidad del suelo. Facultad de Agronomía. Universidad Nacional de La Pampa.